Association of glucose variability at the last day of hospitalization with 30-day readmission in adults with diabetes. Issue 1 (11th May 2020) - Spanakis, Elias K; Singh, Lakshmi G; Siddiqui, Tariq; Sorkin, John D; Notas, George; Magee, Michelle F; Fink, Jeffrey C; Zhan, Min; Umpierrez, Guillermo E
Abstract : Objective: To evaluate whether increased glucose variability (GV) during the last day of inpatient stay is associated with increased risk of 30-day readmission in patients with diabetes. Research design and methods: A comprehensive list of clinical, pharmacy and utilization files were obtained from the Veterans Affairs (VA) Central Data Warehouse to create a nationwide cohort including 1 042 150 admissions of patients with diabetes over a 14-year study observation period. Point-of-care glucose values during the last 24 hours of hospitalization were extracted to calculate GV (measured as SD and coefficient of variation (CV)). Admissions were divided into 10 categories defined by progressively increasing SD and CV. The primary outcome was 30-day readmission rate, adjusted for multiple covariates including demographics, comorbidities and hypoglycemia. Results: As GV increased, there was an overall increase in the 30-day readmission rate ratio. In the fully adjusted model, admissions with CV in the 5th–10th CV categories and admissions with SD in the 4th–10th categories had a statistically significant progressive increase in 30-day readmission rates, compared with admissions in the 1st (lowest) CV and SD categories. Admissions with the greatest CV and SD values (10th category) had the highest risk for readmission (rate ratio (RR): 1.08 (95% CI 1.05 to 1.10), p<0.0001 and RR: 1.11 (95% CI 1.09 to 1.14), p<0.0001 for CV and SD, respectively). Conclusions: Patients with diabetes who exhibited higher degrees of GV on the final day of hospitalization had higher rates of 30-day readmission. Trial registration number: NCT03508934, NCT03877068 .